Racial disparities in access to DBS: results of a real-world U.S. claims data analysis - Frassica, Michael; Kern, Drew S.; Afshari, Mitra; Connolly, Allison T.; Wu, Chengyuan; Rowland, Nathan; Ramirez-Castaneda, Juan; Ushe, Mwiza; Salazar, Claudia; Mason, Xenos (Frontiers in Neurology, 2023)
Introduction Deep brain stimulation (DBS) is an effective and standard-of-care therapy for Parkinson’s Disease and other movement disorders when symptoms are inadequately controlled with conventional medications. It requires expert care for patient selection, surgical targeting, and therapy titration. Despite the known benefits, racial/ethnic disparities in access have been reported. Technological advancements with smartphone-enabled devices may influence racial disparities. Real-world evidence investigations can shed further light on barriers to access and demographic disparities for DBS patients. Methods A retrospective cross-sectional study was performed using Medicare claims linked with manufacturer patient data tracking to analyze 3,869 patients who received DBS. Patients were divided into two categories: traditional omnidirectional DBS systems with dedicated proprietary controllers (“traditional”; n = 3,256) and directional DBS systems with smart controllers (“smartphone-enabled”; n = 613). Demographics including age, sex, and self-identified race/ethnicity were compared. Categorical demographics, including race/ethnicity and distance from implanting facility, were analyzed for the entire population. Results A significant disparity in DBS utilization was evident. White individuals comprised 91.4 and 89.9% of traditional and smartphone-enabled DBS groups, respectively. Non-White patients were significantly more likely to live closer to implanting facilities compared with White patients. Conclusion There is great racial disparity in utilization of DBS therapy. Smartphone-enabled systems did not significantly impact racial disparities in receiving DBS. Minoritized patients were more likely to live closer to their implanting facility than White patients. Further research is warranted to identify barriers to access for minoritized patients to receive DBS. Technological advancements should consider the racial discrepancy of DBS utilization in future developments.